Observer based fault tolerant control for a class of Two-PMSMs systems. (September 2018) - Xiong, Hongyun; Liao, Ye; Chu, Xiaoyan; Nian, Xiaohong; Wang, Haibo
Abstract: In this paper, an observer-based state-feedback fault-tolerant controller is proposed for two coupling permanent magnet synchronous motors (PMSMs) system. The controller compensates the actuator faults and allows the system states to track the reference states corresponding to the output of the original two-PMSMs system. To design such a controller, the information of system actuator faults are required. Then, a robust adaptive observer is designed to estimate the system actuator faults firstly. Next, by setting the reference outputs the equilibrium control inputs and reference speeds are computed based on the mathematic model of the two-PMSMs system. Meanwhile, the variation dynamic model is derived. Additionally, the robust stability of the closed-looped system with fault-tolerant controller is analyzed via the Lyapunov theory and interval matrix. Sufficient stability conditions and the gain matrix of the fault-tolerant controller are obtained by solving the linear matrix inequalities (LMIs). Finally, simulation results are presented to illustrate the effectiveness of the proposed observer and fault tolerant control (FTC) scheme. Highlights: An adaptive observer is designed to estimate the two-PMSMs system actuator faults by LMI techniques and Lyapunov theory. Method of equilibrium states and control inputs is formulated to obtain the variation dynamic model by Taylor expansion. FTC inputs are obtained by multiplying the designed FTC control compensations and the equilibrium control inputs. The proposed observer and controller via LMIs can be easily solved with few adjustable parameters. Simulation results show the tracking performance and robustness of the designed FTC strategy.